2022
DOI: 10.1177/17588359221093745
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the biomarkers and therapies for primary central nervous system lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare and highly aggressive extranodal type of non-Hodgkin lymphoma. After the introduction and widespread use of high-dose-methotrexate (HD-MTX)-based polychemotherapy, treatment responses of PCNSL have been improved. However, long-term prognosis for patients who have failed first-line therapy and relapsed remains poor. Less invasive diagnostic markers, including the circulating tumor DNAs (ctDNAs), microRNAs, metabolomic markers, and other novel biomarkers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 114 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…In recent years, with the introduction of new strategies, such as molecular-targeted drugs, autologous hematopoietic stem cell transplantation (AHSCT) and chimeric antigen receptor T-cell immunotherapy (CAR-T), though the survival rate of PCNSL patients has improved, the overall prognosis of PCNSL is still unsatisfactory. It has been reported that the 5-year OS rate of PCNSL patients is only 15-30%, which undoubtedly increases the economic burden on both patients and society ( 10 , 14 , 28 ).Therefore, a reliable prognostic prediction model which can stratify accurately and guide clinical decisions is of particular importance for patients with PCNSL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the introduction of new strategies, such as molecular-targeted drugs, autologous hematopoietic stem cell transplantation (AHSCT) and chimeric antigen receptor T-cell immunotherapy (CAR-T), though the survival rate of PCNSL patients has improved, the overall prognosis of PCNSL is still unsatisfactory. It has been reported that the 5-year OS rate of PCNSL patients is only 15-30%, which undoubtedly increases the economic burden on both patients and society ( 10 , 14 , 28 ).Therefore, a reliable prognostic prediction model which can stratify accurately and guide clinical decisions is of particular importance for patients with PCNSL.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the treatment of PCNSL is mainly based on high-dose methotrexate (HD-MTX). With the development of new therapeutic strategies such as immunotherapy for novel molecular targets, autologous hematopoietic stem cell transplantation, and CART therapy, the PFS and OS of patients with PCNSL have been improved (10)(11)(12)(13)(14), which may lead to changes in the predictive efficacy of previously developed IELSG and MSKCC scores. Therefore, there is an urgent need for a reliable predictive model suitable for the current stage to predict the survival outcome of PCNSL patients, carry out fine risk stratification, and provide a basis for clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…18,93 Therefore, it is reasonable to hypothesize that PCNSL is sensitive to BTK inhibition. BTK inhibition has been considered as a promising therapeutic approach for PCNSL, as proposed by Zhai et al 94 Currently, except for malignant B cells, Ibrutinib, in combination with XPO1 inhibitor selinexor, also converted the phenotype of tumor-associated macrophages (TAMs), resulting in diminished expression of two regulatory checkpoint receptors on TAMs, PD-1 and SIRPα, which enhanced the anti-tumoral activity of TAMs. 95 Ibrutinib was the first BTK inhibitor evaluated in the trials of PCNSL.…”
Section: Btk Inhibition In Primary Central Nervous System Lymphomamentioning
confidence: 99%